2012
DOI: 10.1093/ijlct/cts069
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic flow channel surface and its impact on PEM fuel cell performance

Abstract: Water management is a critical issue in polymer electrolyte membrane fuel cells (PEMFCs), and it is normally achieved through the modification of surface wettability condition for the cell components. In this study, superhydrophobic surface-coating materials were developed and the gas flow channel surfaces were modified for superhydrophobic surface property with small sliding angles (SAs). The coated surface characteristics were measured, including static contact angle (CA), SA and CA hysteresis as well as sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Previous studies have found that the static contact angle alone is not sufficient to represent the surface dynamic wettability behavior for the description of the liquid water movement on the surface . In a recent study, hydrophobic surfaces were prepared by using the poly(dimethylsiloxane)/silica coatings . It was found that easier water movement on the surface was obtained as the size of the silica particle in the coating material was increased, although the static contact angles measured on the solid surface with different coatings were almost the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the static contact angle alone is not sufficient to represent the surface dynamic wettability behavior for the description of the liquid water movement on the surface . In a recent study, hydrophobic surfaces were prepared by using the poly(dimethylsiloxane)/silica coatings . It was found that easier water movement on the surface was obtained as the size of the silica particle in the coating material was increased, although the static contact angles measured on the solid surface with different coatings were almost the same.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that easier water movement on the surface was obtained as the size of the silica particle in the coating material was increased, although the static contact angles measured on the solid surface with different coatings were almost the same. Therefore, sliding angle is another parameter for the description of the surface dynamic wettability associated with the water transport on the surface . As shown in Figure B, the sliding angle is normally measured as the angle of the surface inclination at which liquid starts to slide on the surface under gravity, and it represents relative easiness of a liquid droplet moving on a surface under a driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the published reports on the channel surface have shown that either hydrophilic or hydrophobic modifications can improve water management for PEMFCs, but their intrinsic mechanisms are quite opposite. It has been demonstrated that the hydrophobic surface is beneficial to water removal in the channel of the bipolar plate because of lower adhesion and greater gas shearing. Wang et al have reported two kinds of surfaces on graphite channels, which are coated with superhydrophobic silica/polydimethylsiloxane composites or superhydrophilic silica. The results show that the superhydrophobic surface has lower adhesion to water, leading to easier water removal.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces are very suitable for use on stainless steel bipolar plates in low-temperature environments due to their unique properties, such as drag reduction [27,28], anticorrosion [29,30], anti-icing [31,32] and self-cleaning [33,34]. The bipolar plate of the superhydrophobic flow channel, under normal operating temperature conditions, can effectively promote the discharge of excess water in the gas diffusion layer and flow channel to improve cell performance [35,36,37]. Therefore, the hydrophobic properties of stainless steel bipolar plates are of great priority in a low-temperature environment.…”
Section: Introductionmentioning
confidence: 99%